Teaching anthropology with and to designers: notes from the field - Roberta Raffaetà (Antropologia, 2020)
This article discusses the Author’s experience of teaching anthropology to and with designers at a Design faculty. Through the illustration of mutual false expectations and productive frictions, the article illustrates the progressive development of a methodology to teach anthropology to designers and to collaborate across disciplines. In so doing, the article also identifies the peculiarities of the ‘anthropological approach’ by emphasizing the importance of cross-scale interactions in the analysis of phenomena and the role of theory in making ethnography and, therefore, in supporting designers to make their work. The main argument is that theory and practice are not dichotomous, rather they are co-implicated because theoretical innovation is at the basis for design practices. The article concludes explicating the ways in which anthropology can be useful to design students, even if in forms that are different from those usually expected or imagined.